Spatial language and converseness. Issue 12 (December 2016) - Burigo, Michele; Coventry, Kenny R.; Cangelosi, Angelo; Lynott, Dermot
Typical spatial language sentences consist of describing the location of an object (the located object) in relation to another object (the reference object) as in "The book is above the vase". While it has been suggested that the properties of the located object (the book) are not translated into language because they are irrelevant when exchanging location information, it has been shown that the orientation of the located object affects the production and comprehension of spatial descriptions. In line with the claim that spatial language apprehension involves inferences about relations that hold between objects it has been suggested that during spatial language apprehension people use the orientation of the located object to evaluate whether the logical property of converseness (e.g., if "the book is above the vase" is true, then also "the vase is below the book" must be true) holds across the objects' spatial relation. In three experiments using sentence acceptability rating tasks we tested this hypothesis and demonstrated that when converseness is violated people's acceptability ratings of a scene's description are reduced indicating that people do take into account geometric properties of the located object and use it to infer logical spatial relations.